Survival of pathogens on soybean debris under no-tillage and conventional tillage systems - Almeida, Álvaro Manuel Rodrigues; Saraiva, Odilon Ferreira; Farias, José Renato Bouças; Gaudêncio, Celso Almeida; Torres, Eleno (Pesquisa Agropecuaria Brasileira, 2001)
A study was conducted in the subtropical area of Southern Brazil to determine the survival of pathogens in soybean residues under conventional and no-tillage cultivation systems from March to September of 1998 and 1999. The pathogens most frequently isolated were Colletotrichum truncatum, Phomopsis spp., Cercospora kikuchii, Fusarium spp., Macrophomina phaseolina, and Rhizoctonia solani. Other fungi isolated were Myrothecium roridum, Penicillium sp., Chaetomium sp., Epicoccum sp., Corynespora cassiicola and Trichoderma sp. The percent of survival of each pathogen varied according to the month and the year. Survival of C. truncatum, Phomopsis spp. and C. kikuchii were significantly reduced (p < 0.05) from the first to the last evaluation either on buried debris or maintained on the soil surface. On the other hand, M. phaseolina and Fusarium spp. were either not affected or favored by burying the debris. The frequency of recovery of Fusarium spp. increased specially in debris kept under the soil. The loss of biomass, measured by debris weight along the period of this study, showed a reduction of 44.4% in the conventional system and 34.9% in the no-tillage system in 1998, when rain was better distributed. In 1999, the reduction was 48.2% and 39.0% for the conventional and no-tillage system, respectively.
Keywords: cultivation; crop residues; degradation; biomass; plant diseases